"Sound Finances": Strategy or Soundbite. (August 2017) - McMahon, Michael
A defining feature of (at least) the last three general elections has been the emphasis placed on each political party's fiscal credibility and their ability to deliver "sound public finances". Applying the logic of household book-keeping, balancing the fiscal budget is said to capture such soundness. There is, however, little evidence that a balanced budget is necessarily sound. Instead, the evolution of public finances depends on (1) both the fiscal choices made on the level of spending and taxation, (2) the underlying growth of the economy which depends on far more than the fiscal decisions, and (3) interest rates on government debt and the financing needs of the government. As the economic situation changes, so too does the likely path of debt to GDP and hence the possible fiscal options open to a country. Sticking to the soundbite of "sound finances" has often distracted from the underlying menu of political choices and as such is a disruptive narrative in UK economics today.